Predicting model of academic buoyancy: the roles of achievement goals and self-regulation - Mohd. Rameli, Mohd. Rustam (2014)
The existence of challenges in learning Mathematics is an undeniable reality. The challenges come from various sources and each of the sources can affect students’ learning progress in certain ways. To ensure students are able to pursue their academic goals, it is important to identify students’ ability to overcome the academic challenges that they face. Students’ capacity to overcome their daily academic challenges is known as academic buoyancy. Academic buoyancy acts as a protective element to make students persist in the learning process. This paper suggests a model of academic buoyancy in Mathematics where achievement goal orientations and self-regulation are the two individual characteristics postulated as the predictors. The Bigg’s 3P model of effective learning is used as the basis of the model. The 3P model involves two main phases (presage and process) which will determine students’ learning outcomes. In the model proposed in this paper, achievement goal orientation presages students’ selfregulation process which will then influence students’ academic buoyancy in Mathematics. The suggested model can become a guideline for teachers, parents and academic practitioners in assisting students in facing daily academic challenges in the Mathematics.